Density of Streptococcus mutans biofilm protein induced by glucose, lactose, soy protein and iron - Indah Listiana Kriswandini; Indeswati Diyatri; Intan Amalia Putri (Universitas Airlangga, 2019)
Background: Caries constitute an infectious disease that result from the interaction of bacteria with the host and the oral environment. Streptococcus mutans (S. mutans) represents the main bacterium that causes caries. The ability of S. mutans to form biofilms in the oral cavity is influenced by daily nutrient intake. This study of bacterial biofilm proteins can be used in the manufacture of kits for the detection of infectious diseases such as caries in the oral cavity. A biomarker is required for the manufacture of the detection kit. Consequently, research must first be conducted to determine the molecular weight and density of S. mutans biofilm proteins induced by several different daily nutrients, namely; 5% glucose, 5% lactose, soy protein and 5% iron. Purpose: This study aimed to analyse the density of S. mutans biofilm protein induced by 5% glucose, 5% lactose, soy protein, and 5% iron. Methods: The density of the S. mutans biofilm protein bands induced were measured using EZ Imager Gel DocTM software. Results: A band of biofilm protein (61.7 kDa) was obtained from S. mutans induced by 5% glucose, four bands of biofilm protein (180 kDa; 153,9 kDa; 43,9 kDa; 37,5 kDa) from 5% lactose induction and seven bands of biofilm protein (157,9 kDa; 86,6 kDa; 66,5 kDa; 50,1 kDa; 37,9 kDa; 32,3 kDa; 29,4 kDa) from soy protein induction. In contrast, S. mutans induced by 5% iron did not show any protein bands. The proteins that result from each inducer are of differing densities. Conclusion: The protein bands from each inducer are of different densities which can be used in the further test to make a biomarker for dental caries detection kits.